2013
DOI: 10.1139/cjb-2013-0112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coflowering Mimulus ringens on phenotypic selection on floral traits of gynodioecious Lobelia siphilitica

Abstract: Although interspecific competition for pollination is hypothesized to result in divergence in floral traits (i.e., character displacement), few studies have tested whether selection on these traits differs in the presence and absence of a competitor for pollination. We measured phenotypic selection on floral traits of Lobelia siphilitica growing in the presence and absence of Mimulus ringens, a potential competitor for pollination. Because L. siphilitica is gynodioecious, we estimated selection separately for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 46 publications
(65 reference statements)
1
29
0
Order By: Relevance
“…). For example, a recent meta‐analysis found that presence of co‐flowering plants does not significantly reduce seed and fruit production (Charlebois and Sargent ), suggesting that manipulating co‐flowering plants should have a relatively small effect on selection on floral traits (e.g., Wassink and Caruso ). Alternatively, other biotic factors could have a relatively small effect on selection because variation in floral traits has a weaker effect on the probability of antagonistic and/or competitive interactions than on pollination (e.g., Sandring and Ågren ).…”
Section: Discussionmentioning
confidence: 99%
“…). For example, a recent meta‐analysis found that presence of co‐flowering plants does not significantly reduce seed and fruit production (Charlebois and Sargent ), suggesting that manipulating co‐flowering plants should have a relatively small effect on selection on floral traits (e.g., Wassink and Caruso ). Alternatively, other biotic factors could have a relatively small effect on selection because variation in floral traits has a weaker effect on the probability of antagonistic and/or competitive interactions than on pollination (e.g., Sandring and Ågren ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this difference in flower production, females also produce significantly more fruits and seeds per plant than hermaphrodites (Caruso and Yakobowski ). However, the number of seeds per fruit does not differ between females and hermaphrodites (Caruso and Yakobowski ; Wassink and Caruso ).…”
Section: Methodsmentioning
confidence: 99%
“…Such properties include flower thickness, the dense packing of cells via veins or thin cell layers, the curvature in the epidermal layer, and irregularly shaped granules with high refractive indices van der Kooi et al 2016van der Kooi et al , 2017. Ecological studies theoretically investigating brightness often involve pollinator-mediated selection experiments, where selection pressures towards specific colour traits are quantified (Caruso et al 2010;Renoult et al 2013;Wassink and Caruso 2013;Sletvold et al 2016). Such studies provide some evidence that brightness may be important for pollinators.…”
Section: Open Accessmentioning
confidence: 99%